ANALYSIS OF MARKET ANOMALY JANUARY EFFECT ON PROPERTY AND REAL ESTATE STOCK ISSUERS IN INDONESIA - Muhammad Dava Rizki; Ghazali Syamni; Husaini; Darmawati Mukhtar (PT. Radja Intercontinental Publishing, 2024)
This study was conducted to analyze the behavior of the January Effect on property and real estate companies on the Indonesia Stock Exchange. The data used are secondary data on 74 property and real estate companies daily using purposive sampling techniques. All data are accessed from www.idx.co.id and. All data has been collected and tabulated in the form of monthly data. The data analysis method used is the Mann-Whitney difference test method. The results of the study found that there was no significant abnormal return. Thus, the findings of this study indicate that there was no January Effect phenomenon, meaning that the market is efficient.